2004
DOI: 10.1139/x03-226
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Pinus radiata zygotic embryo cotyledons: effect of storage duration on adventitious shoot formation and plant growth after 2 years in the field

Abstract: This work is the first report of the cryopreservation of conifer cotyledons without cryoprotectants and their subsequent shoot regeneration and successful establishment of a field trial. Multiple genotypes of radiata pine (Pinus radiata D. Don) embryo cotyledons were stored in liquid nitrogen following a desiccation treatment. Cotyledons that had been stored in liquid nitrogen for 7, 14, and 28 days were compared with noncryopreserved cotyledons for adventitious shoot production, root formation on the shoots, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…short-or long-term tissue culture or different cryopreservation protocols had no effect on the growth of the regenerated plants. In woody plants, the only report of the potential effect of cryopreservation on growth of regenerated plants is published by Hargreaves et al (2004). They found the height growth of radiata pine (Pinus radiata D. Don) similar both following cryopreservation and micropropagation.…”
Section: Discussionmentioning
confidence: 99%
“…short-or long-term tissue culture or different cryopreservation protocols had no effect on the growth of the regenerated plants. In woody plants, the only report of the potential effect of cryopreservation on growth of regenerated plants is published by Hargreaves et al (2004). They found the height growth of radiata pine (Pinus radiata D. Don) similar both following cryopreservation and micropropagation.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that partially desiccated cotyledons of P. radiata, detached from mature zygotic embryos, can be cryopreserved without cryoprotectant pretreatment with one-step cooling. After up to 28 days in cryopreservation, the thawed cotyledons produced the same number of adventitious shoots and plants as the noncryopreserved control cotyledons, but plant height was 8% lower in the cryopreserved material after 21 months in the field (Hargreaves et al 2004). Subsequently, it was found that more genotypes were captured by culture of cryopreserved cotyledons than were obtained from axillary shoots arising from epicotyls of the noncryopreserved parts of the same zygotic embryo (Hargreaves et al 2005).…”
Section: Organogenesismentioning
confidence: 93%
“…This is not long enough for a proper field test. The ability to cryopreserve material for propagation by organogenesis is desired for species for which organogenesis provides plantlets for a large number of genotypes per family, whereas SE does so for only a limited number of genotypes within the family (Hargreaves et al 2004(Hargreaves et al , 2011. It was found that partially desiccated cotyledons of P. radiata, detached from mature zygotic embryos, can be cryopreserved without cryoprotectant pretreatment with one-step cooling.…”
Section: Organogenesismentioning
confidence: 99%
“…The adventitious-axillary organogenesis shoots were prepared from excised cotyledons that were cryopreserved at − 196°C and then had shoots initiated adventitiously. Non-germinated hypocotyls (including epicotyls) from the embryos that provided the cotyledons for cryopreservation were retained and these provided the noncryopreserved epicotyl-axillary shoots, thus material was available from two methodology origins using the same genotypes (Hargreaves et al 2004(Hargreaves et al , 2005. Mature material was established using techniques described by Horgan and Holland (1989).…”
Section: Tissue Culture Preparationmentioning
confidence: 99%